Triglyceride-glucose index is a predictor of the risk of prostate cancer: a retrospective study based on a transprostatic aspiration biopsy population - Zhou, Yijie; Li, Tianqi; Muheiyati, Guliman; Duan, Yajun; Xiao, Songtao; Gao, Yi; Tao, Ning; An, Hengqing (Frontiers in Endocrinology, 2024)
BackgroundCurrent research suggests that prostate cancer (PCa), one of the most common cancers in men, may be linked to insulin resistance (IR).Triglyceride-glucose index (TyG index) was made for a marker of insulin resistance. We investigated the relationship between the TyG index and the risk of PCa.ObjectiveTo assess the correlation and dose-response relationship between TyG index and prostate cancer.MethodRetrospectively, 316 patients who required prostate biopsy puncture in the First Affiliated Hospital of Xinjiang Medical University from March 2017 to July 2021 were collected, and the relationship between factors such as the TyG index and prostate cancer was analyzed by Logistic regression model combined with a restricted cubic spline.Results(1) The differences in age, initial PSA and TyG index between the two groups were statistically significant; (2) Logistic regression results showed that the risk of prostate cancer in the highest quartile of the TyG index (Q4) was 3.387 times higher than that in the lowest quartile (Q1) (OR=3.387,95% CI [1.511,7.593], P=0.003); (3) The interaction results showed a significant interaction between the TyG index Q4 group and age with the risk of developing prostate cancer (P for interaction<0.001). (4) The results of the restricted cubic spline showed a linear dose-response relationship between the TyG index and the risk of prostate cancer; (5) The Receiver operating characteristic (ROC) curve results showed that the area under the curve (AUC) of the TyG index combined with initial PSA and age was 0.840, with a sensitivity and specificity of 62.5% and 93.3%, respectively.ConclusionTyG index and age are risk factors for prostate cancer, and the interaction between the TyG index and different risk factors may increase the risk of prostate cancer. TyG index has some predictive value for the risk of prostate cancer, and the risk of prostate cancer can be reduced by controlling the levels of blood lipids and blood glucose.